2019
DOI: 10.1063/1.5087625
|View full text |Cite
|
Sign up to set email alerts
|

Supercavitation phenomenon research of projectiles passing through density change area

Abstract: The past research on the supercavity flow mostly focused on the homogeneous fluid medium, ignoring the influence of the sudden change of the medium density. We present results from numerical study of moving projectile passing density change zone, both from low-density zone to high-density zone and from high-density to low-density. Particular attention is given to the cavity variation when projectile voyaging through different liquid density areas. And the influence of the cavitation number on the cavity variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Zhan et al studied the influence of lateral flow on supercavitation and concluded that the cavity morphology is symmetrical in the absence of lateral flow and asymmetrical in the presence of lateral flow, with the cavity morphology increasing with the velocity . Fan et al studied the change in supercavitation when the projectile passes through different density regions and found that the diameter contraction of the projectile occurs through different density regions and in different locations and is related to the density degree . Zhan et al studied the influence of different wave phases and heights on the supercavitation flow field and found that the wave phases and height affect the resistance of supercavitation .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhan et al studied the influence of lateral flow on supercavitation and concluded that the cavity morphology is symmetrical in the absence of lateral flow and asymmetrical in the presence of lateral flow, with the cavity morphology increasing with the velocity . Fan et al studied the change in supercavitation when the projectile passes through different density regions and found that the diameter contraction of the projectile occurs through different density regions and in different locations and is related to the density degree . Zhan et al studied the influence of different wave phases and heights on the supercavitation flow field and found that the wave phases and height affect the resistance of supercavitation .…”
Section: Introductionmentioning
confidence: 99%
“… 18 Fan et al studied the change in supercavitation when the projectile passes through different density regions and found that the diameter contraction of the projectile occurs through different density regions and in different locations and is related to the density degree. 19 Zhan et al studied the influence of different wave phases and heights on the supercavitation flow field and found that the wave phases and height affect the resistance of supercavitation. 20 Jiang et al carried out experimental research on ventilated supercavitation injected with high-temperature gas, concluded that the length of the supercavitation would increase under the injection of high-temperature gas, and obtained a theoretical model of the thermodynamic effects.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 studied the influence of free liquid on the cavity shape of the moving body and the flow field in the cavity through experiments and numerical methods. 9,10 used numerical methods to study the characteristics of supercavitation flow under complex environmental interference. The study obtained the law of the influence of environmental factors, such as density mutations and seabed obstacles, on the development of supercavitation morphology.…”
Section: Introductionmentioning
confidence: 99%
“…In studying the problem of torpedo failure, Gilbarg and Anderson (1948) experimentally analyzed how different factors depend on the waterentry cavity, and found that air density has a significant effect on the closing time of the cavity surface near the point of water entry. In recent years, some researchers have studied the cavity changes of projectiles when the projectiles navigate in regions of different liquid density (Fan et al 2019). Some researchers have also proved that density is an important factor in materials and has a certain influence on the range and power of projectile , both experimentally and theoretically (Forouzani et al 2018;Sorensen et al 2008;Wang et al 2020;Zhang et al 2021).…”
Section: Introductionmentioning
confidence: 99%